Resource-Based View Analysis of Innovation and Performance in Brazilian Certified Soybean Seed Companies - José Mauricio da Silva; Ketelen Favero; Vitor Francisco Dalla Corte (Journal of Technology Management & Innovation, 2025)
This research, grounded in the Resource-Based View (RBV), investigated the relationship between organizational resources, innovation, and performance in certified soybean seed producing companies. Employing a quantitative, descriptive, and cross-sectional methodology, the study used a survey administered to 30 companies formally registered with the Brazilian Ministry of Agriculture. The hypotheses tested explored the influence of resources on innovative capacity and organizational performance. Results indicated that strategic resources shape market-oriented innovative practices, highlighting a demand-pull innovation process. Despite sample limitations, the study provides significant theoretical and practical contributions, suggesting actionable directions for the sector.